DAMPAK MOTIVASI BELAJAR DAN REGULASI DIRI TERHADAP PROKRASTINASI - Ratnasartika Aprilyani (POLITEKNIK LP3I JAKARTA, 2022)
This study aims to determine the effect of learning motivation and self-regulation with academic procrastination that occurs in students who work at University X Jakarta. The subjects in this study were working students of University X Jakarta, totaling 100 with quantitative research methods. Sampling used is simple random sampling technique. This research instrument uses three psychological scales, namely the academic procrastination scale (APS), the learning motivation scale, and the self-regulation questionnaire scale (SRQ). Data analysis used multiple linear regression analysis. The results of the first hypothesis test indicate that there is a significant negative effect between learning motivation and academic procrastination, so the hypothesis is accepted. The results of the second hypothesis test show that there is no influence between self-regulation and academic procrastination, so the hypothesis is rejected. The third hypothesis shows that there is an influence between learning motivation and self-regulation on academic procrastination, so the hypothesis is acceptedKey words: Learning Motivation, Self-Regulation, Academic Procrastination